Exploring brain glutathione and peripheral blood markers in posttraumatic stress disorder: a combined [1H]MRS and peripheral blood study - Watling, Sarah E.; Rhind, Shawn G.; Warsh, Jerry; Green, Duncan; McCluskey, Tina; Tong, Junchao; Truong, Peter; Chavez, Sofia; Richardson, J. Don; Kish, Stephen J.; Boileau, Isabelle (Frontiers in Psychiatry, 2023)
Introduction Oxidative stress has been implicated in psychiatric disorders, including posttraumatic stress disorder (PTSD). Currently, the status of glutathione (GSH), the brain's most abundant antioxidant, in PTSD remains uncertain. Therefore, the current study investigated brain concentrations of GSH and peripheral concentrations of blood markers in individuals with PTSD vs. Healthy Controls (HC). Methods GSH spectra was acquired in the anterior cingulate cortex (ACC) and dorsolateral prefrontal cortex (DLPFC) using MEGA-PRESS, a J-difference-editing acquisition method. Peripheral blood samples were analyzed for concentrations of metalloproteinase (MMP)-9, tissue inhibitors of MMP (TIMP)-1,2, and myeloperoxidase (MPO). Results There was no difference in GSH between PTSD and HC in the ACC (n = 30 PTSD, n = 20 HC) or DLPFC (n = 14 PTSD, n = 18 HC). There were no group differences between peripheral blood markers (P > 0.3) except for (non-significantly) lower TIMP-2 in PTSD. Additionally, TIMP-2 and GSH in the ACC were positively related in those with PTSD. Finally, MPO and MMP-9 were negatively associated with duration of PTSD. Conclusions We do not report altered GSH concentrations in the ACC or DLPFC in PTSD, however, systemic MMPs and MPO might be implicated in central processes and progression of PTSD. Future research should investigate these relationships in larger sample sizes.